Produccion de jitomate en doseles escaleriformes bajo invernadero - Vazquez Rodriguez, J.C.=700 1 Sanchez del Castillo, F.; Moreno Perez, E del C.
(En, Es)
ilus., 17 ref.
Keywords: LYCOPERSICON ESCULENTUM; ESPACIAMIENTO; PRODUCCION; PRODUCTIVIDAD; RENDIMIENTO; ESTRATO VEGETAL; PODA; CULTIVO HIDROPONICO; RADIACION SOLAR; MEXICO